Radiogram from Georg Bredig to Max Bredig, September 18, 1939 - Bredig, Georg (1939)
Georg Bredig (1868-1944) informs his son, Max Bredig (1902-1977), of his current address in Bleicherode, Germany.
Keywords: Bredig, Georg, 1868-1944; Bredig, Max Albert, 1902-1977